A pilot study to evaluate the combination of surgery and brachytherapy for local tumor control in young children with perianal rhabdomyosarcoma - Andreas Schmidt; David Baumann; Ulf Lamprecht; Benjamin Mayer; Cristian Urla; Benjamin Bender; Jürgen Schäfer; Frank Fideler; Maximilian Niyazi; Frank Paulsen; Jörg Fuchs (Clinical and Translational Radiation Oncology)
Background: Perianal rhabdomyosarcoma ((P)RMS) are rare and have a poor prognosis. Data in young children are limited and local therapy is not well defined. Combined brachytherapy and surgery is routinely being used for RMS at other sites in children as it provides good oncologic outcomes and allows for organ-sparing surgery. The objective of this study was to evaluate this combination treatment for local tumor control and organ-sparing surgery in young children with (P)RMS. Methods: A retrospective review of the medical records of all children who underwent surgery and brachytherapy for (P)RMS at our institution since 2009 was conducted. Results: Surgery for (P)RMS was performed in 6 patients at a median age of 19 months (range 8–50). Embryonal RMS was diagnosed in 4 patients and alveolar RMS in 2 patients, of which 1 patient had FOXO1 fusion-positive RMS. All patients underwent postoperative high-dose rate (HDR) brachytherapy. Organ-preserving surgery was achieved in 5 of 6 patients (83 %). In 1 patient, the entire sphincter was infiltrated, making organ-preserving resection impossible. 5 of 6 patients (83 %) exhibited an event-free and overall survival at a median follow-up of 26 months (range 8–107). One patient died due to locoregional recurrence. Complications were urethral leakage in 1 patient followed by urethral stenosis and delayed wound healing and vaginal stenosis in another patient. No patient reported fecal incontinence. Conclusions: Combined treatment with surgery and HDR brachytherapy is feasible in very young children with (P)RMS and leads to a favorable oncologic outcome. Preliminary data show a good functional preservation.